La formation des paysagistes au premier Congrès international des architectes de jardins (1937) - Luisa Limido; Chiara Santini (Projets de Paysage)
The first International Congress of Garden Architects, organised in Paris as part of the 1937 International Exhibition of Arts and Technologies by the French Society of Garden Architects (Société française des architectes de jardins, SFAJ), marked the initial phase in a collective reflection on the objectives and challenges in the training of landscape architects in Europe. Following the economic, political and social crisis caused by the First World War, the crisis of 1929, and the rise of a new public demand for open spaces for leisure, sports, and recreational activities, garden architects were called on to address profound changes in the commissioning and in the typology, objectives, and scale of landscape projects. Based on original hitherto unstudied documents held in the archives of the Association Henri & Achille Duchêne this article presents the initiatives that led to the organisation of the Congress and how it made a defining contribution in the training of French landscape architects.